Prática de Análise Linguística nos anos finais do Ensino Fundamental: desafios e possibilidades - Mattei, Isabel (2016)
This dissertation aims to develop a work with Linguistic Analysis focused especially on textual rewriting, starting from a theoretical rescue of the theme, which was analyzed from three perspectives: the academic productions, the official curricular documents destined to the Teaching of Portuguese Language and the productions of teachers of Basic Education. Therefore, the following motivational questioning is used: do the theoretical productions on Linguistic Analysis clarify the referral of this practice in primary education and contribute to the writing and rewriting of students' texts at this level of education? We chose, as a foundation for the study, the theoretical assumptions based on the interactionist conception of language (BAKHTIN, 2014) and its applications to teaching proposed by Geraldi (1984, 1997, 1999) and Riolfi (2010), among others. It will also be used as theoretical support sources that, in the discussions about writing production and rewriting of texts in the school context, adopt the conception of language defended herein. The research, anchored in the assumptions of Applied Linguistics, Assumes a qualitative data approach, of an interpretative nature, linked to the action-research method, either for the interest in discussing the pedagogical practice or for the stage of practical application of Linguistic Analysis activities with students of the Fundamental Level. In order to fulfill the PROFLETRAS requirement - preparation, application of didactic material and analysis of the results -, the proposal was applied in a 9th grade class and the practice of Linguistic Analysis associated to the work of writing texts of the personal story genre. For the generation of data of the activities applied, the field diary was used as an instrument and, for data analysis; the choice was for the contents or learning processes as a reference for reflection on pedagogical practice (ZABALA, 2010). In the process of rewriting the students texts, from a previously organized work, we notice considerable advances in relation to the initial writing of the selected genre. Therefore, the results of the application of the pedagogical proposal demonstrated that a planned work that combines the research with the classroom practice presents a great possibility of effecting the practice of Linguistic Analysis in the Portuguese Language classes